2016
DOI: 10.1016/j.brat.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The desire to belong: Social identification as a predictor of treatment outcome in social anxiety disorder

Abstract: Objective Perception of personal identity cannot be separated from the perception of the social context and one's social identity. Full involvement in group psychotherapy may require not only the awareness of personal impairment, but also social identification. The aim of the current study was to examine the association between social identification and symptom improvement in group-based psychotherapy. Method 169 participants received 12 sessions of group-based cognitive behavioral therapy for social anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
4
12
0
Order By: Relevance
“…Whilst this research has not examined the role played by practitioners, heightened social identification on the part of clients has been found to be associated with decreased severity of social anxiety over time. Moreover, in both the Cruwys, Haslam, Dingle, Jetten, et al (2014) and Meuret et al (2016) studies, the presence of social identification was ultimately linked to subsequent positive therapeutic outcomes for clients, just as the presence of a working alliance has consistently been linked to the same positive outcomes in therapy.…”
Section: The Social Identity Approach: Why a Shared Sense Of “Us” Is ...mentioning
confidence: 96%
See 1 more Smart Citation
“…Whilst this research has not examined the role played by practitioners, heightened social identification on the part of clients has been found to be associated with decreased severity of social anxiety over time. Moreover, in both the Cruwys, Haslam, Dingle, Jetten, et al (2014) and Meuret et al (2016) studies, the presence of social identification was ultimately linked to subsequent positive therapeutic outcomes for clients, just as the presence of a working alliance has consistently been linked to the same positive outcomes in therapy.…”
Section: The Social Identity Approach: Why a Shared Sense Of “Us” Is ...mentioning
confidence: 96%
“…Social identification has similarly been linked to improved outcomes in the treatment of other conditions including social anxiety disorder (e.g., Meuret et al, 2016). Whilst this research has not examined the role played by practitioners, heightened social identification on the part of clients has been found to be associated with decreased severity of social anxiety over time.…”
Section: The Social Identity Approach: Why a Shared Sense Of “Us” Is ...mentioning
confidence: 99%
“…family, school, and friendship groups) was associated with better mental health. Finally, in an intervention study, Meuret et al (2016) showed positive effects of group-based cognitive therapy for social anxiety on feelings of closeness to others, which in turn were related to clinical outcomes. In sum, identification with social categories is a predictor of individuals’ health and well-being (Haslam et al, 2018).…”
Section: The Social Identity Approachmentioning
confidence: 98%
“…Induction of strong experiences of interconnection and feelings of closeness with others may create more enduring shifts toward a sense of shared humanity and interconnection with others, which may be helpful for people with SAD who typically feel different from and inferior to others, disconnected, prone to rejection, and lonely. One study of people in treatment for SAD found that people who reported seeing themselves as closer to others had better treatment outcomes, suggesting that shifts toward a greater sense of closeness and similarity to others may improve outcomes (Meuret et al., 2016)…”
Section: Possible Processes Of Change In Mdma‐at For Social Anxiety D...mentioning
confidence: 99%
“…Induction of strong experiences of interconnection and feelings of closeness with others may create more enduring shifts toward a sense of shared humanity and interconnection with others, which may be helpful for people with SAD who typically feel different from and inferior to others, disconnected, prone to rejection, and lonely. One study of people in treatment for SAD found that people who reported seeing themselves as closer to others had better treatment outcomes, suggesting that shifts toward a greater sense of closeness and similarity to others may improve outcomes (Meuret et al, 2016) Some of the self-transcendent emotions and experiences in MDMA-AT may occur in the form of self-compassion, which is likely to be particularly helpful in relation to the high levels of shame experienced by people with SAD. Experimental research has shown that self-compassion increases when people take MDMA/ecstasy (Kamboj et al, 2015(Kamboj et al, , 2018 and experiences with self-compassion are commonly reported in MDMA-AT as shown in qualitative reports like, "It was really that first MDMA session that we had…where I was able to clearly see that I had a big disconnect in compassion that I had for myself.…”
Section: Self-transcendent Experiences and Emotionsmentioning
confidence: 99%